Comparative evaluation of postoperative pain intensity after single-visit and multiple-visit retreatment cases: a prospective randomized clinical trial - Hatice Miray Uyan; Keziban Olcay; Mutlu Özcan (Brazilian Dental Science)
Objective: This study was designed to evaluate postoperative pain after endodontic retreatment. Material and Methods: Asymptomatic, multi-rooted molar & premolar teeth requiring retreatment with 2–5 mm periapical lesions were included. Seventy-eight teeth were randomly placed in four groups (n=20): single-visit (control, group 1), Ledermix (group 2), metronidazole, ciprofloxacin, minocycline mixture (group 3), calcium hydroxide (group 4). The postoperative pain was recorded using a VAS at 6, 12, 24, and 48 h after retreatment. Statistical evaluation was performed using Two-Way Repeated Measures ANOVA and Tukey test. Results: Mild pain occurred in 67.5%, moderate in 30%, and flare-ups in 2.5%, and there was a significant difference between the groups (p<0.01). Significantly lower postoperative pain was observed in TAP and CaOH2 groups(p<0.05). In the 6, 12, and 24 h intervals, there was a significant difference in the pain levels (p<0.05). Conclusion: TAP and CaOH2 are effective for reducing postoperative pain after retreatment.